1989
DOI: 10.1080/03670244.1989.9991104
|View full text |Cite
|
Sign up to set email alerts
|

Energy and macronutrient intake of New Zealand adolescents

Abstract: During the months of April and May (autumn season in the Southern hemisphere) 1985, a 3-day 24-hour dietary recall was collected from 255 female and 246 male third form students (12-14 years old) from secondary schools of an urban region in the South Island of New Zealand. Energy and macronutrient intake information was derived from this recall data.The median intake of energy for girls was 7.5 MJ and boys 10.1 MJ. Although these intakes were only 83% and 92% of the daily recommended energy levels for girls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1994
1994
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…Intakes were similar to adult intakes of fat estimated in 1986/1987 in this population by 7 d weighed dietary records (Strain et al 1990). These levels of total fat intake were also similar to those estimated for Finnish (Rasanen et al 1991) and New Zealand (Tan et al 1989) adolescents but above those estimated for British (Department of Health, 1989), Dutch (Van Poppel et al 1991), French (Michaud et al 1991) and Irish (Lee & Cunningham, 1990) counterparts of the same age using various dietary intake methodologies. Although the possible relationship between high fat intake and the development of obesity is currently a subject of debate (Leibel, 1992), low-fat diets have been shown to be valuable in the management of established obesity (Royal College of Physicians, 1983).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Intakes were similar to adult intakes of fat estimated in 1986/1987 in this population by 7 d weighed dietary records (Strain et al 1990). These levels of total fat intake were also similar to those estimated for Finnish (Rasanen et al 1991) and New Zealand (Tan et al 1989) adolescents but above those estimated for British (Department of Health, 1989), Dutch (Van Poppel et al 1991), French (Michaud et al 1991) and Irish (Lee & Cunningham, 1990) counterparts of the same age using various dietary intake methodologies. Although the possible relationship between high fat intake and the development of obesity is currently a subject of debate (Leibel, 1992), low-fat diets have been shown to be valuable in the management of established obesity (Royal College of Physicians, 1983).…”
Section: Discussionsupporting
confidence: 82%
“…Average carbohydrate intake was 49 YO of EI while average dietary fibre intakes were the same as other adolescent groups in Finland (Rasanen et al. 1991) and New Zealand (Tan et al 1989).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Interpretation of the results is complicated by the fact that no reference standards for Nigerian subjects are available. However, in comparison with values reported in similar studies in Borno State, Nigeria (Oguntona et al 1987), USA (Garn et al 1985;Pao et al 1985), UK (Hackett et al 1983) Australia (McNaughton & Audrey, 1970Woodward et al 198l), New Zealand (Tan et al 1989) and Northern Ireland (Barker et al 1989) the EI values observed in the present study were low. The FAO/WHO/UNU (1985) recommendations specify that adolescent girls aged 11-17 years require, on average, 8318kJ(1988 kcal)/d.…”
Section: Energy and Nutrient Intakescontrasting
confidence: 47%